Genetic Polymorphism in Patients with Diabetic Nephropathy and Retinopathy: A Cross-sectional Study - Gupta, Parul; Madhu, Sri Venkata; Bubber, Parvesh (Journal of clinical and diagnostic research, 2023)
Introduction: The chronic persistence of diabetes leads to microvascular complications, such as Diabetic Nephropathy (DN) and Diabetic Retinopathy (DR). Both of these are progressive disorders involving pathological changes in capillaries. A few biochemical pathways have been suggested to link hyperglycaemia and microvascular complications. The probability of developing and progressing DN and DR is associated with the duration of diabetes. These complex disorders are strongly influenced by both genetics and environmental factors. Several candidate genes have been reported to be associated with DN and DR in different populations. Aim: To determine the co-existence of DN and DR in relation to gene polymorphisms of Angiotensin-Converting Enzyme (ACE), Angiotensinogen (AGT), Receptor for Advanced Glycation End-products (RAGE), Aldose reductase (ALR2), and Vascular Endothelial Growth Factor (VEGF). Materials and Methods: The present DN and DR cross-sectional study was conducted at the Department of Endocrinology, University College of Medical Sciences, University of Delhi and GTB, New Delhi, India, and the Discipline of Biochemistry, Indira Gandhi National Open University, New Delhi, India. The study was conducted from October 2019 to August 2022. All the participants under uniform diabetes management were divided into two groups (100 in each group): Group 1 included Type-II diabetic patients with DN and DR, and Group 2 comprised Type-II diabetic patients with DN only. Polymorphisms in all genes were determined using Polymerase Chain Reaction (PCR), followed by digestion with restriction enzymes and visualisation through an ultraviolet transilluminator. The analysis of biochemical parameters and association of gene polymorphisms was performed using Statistical Package for Social Sciences (SPSS) version 26.0 software. Results: There were 57 males and 43 females in the DN+DR group, and 51 males and 49 females in the DN-DR group. The mean age of study subjects in the DN+DR group was 52.60±9.08 years, compared to the DN-DR group (47.33±10.68 years). The DN+DR group had a significantly higher mean duration of diabetes (11.78±6.86 vs. 5.13±4.78, p≤0.001) and a significantly lower mean waist circumference (91.30±13.99 vs. 95.11±9.95 cm, p≤0.02). The DN+DR group also had significantly higher urea (34.34±16.32 vs. 26.43±12.34 cm, p≤0.001), creatinine (1.34±0.90 vs. 0.89±0.25 cm, p≤0.03) and significantly lower estimated Glomerular Filtration Rate (eGFR) levels compared to the DN-DR group. The distribution of genotypes of ALR2 (p≤0.04) and VEGF genes (p≤0.001) showed a significant difference between both DN+DR and DN-DR groups. The frequency of the D allele of the VEGF gene (p≤0.02) (OR=1.94, 95% Confidence Interval (CI)=1.10-3.40) was higher in the DN+DR group. The DN+DR group also had a significantly lower frequency of the CT+TT dominant model of the ALR2 gene (p≤0.04) as well as an increased frequency of the ID+DD dominant model of the VEGF gene (p≤0.002). No significant differences were found in genotypic as well as allelic frequencies of ACE, AGT, and RAGE gene polymorphisms between the two groups. Conclusion: The D allele of the VEGF (I/D) gene polymorphism is significantly associated with DR in patients with DN. It can be concluded that the VEGF gene plays an important role in the development of retinopathy in DN patients.